ANALISIS DATA POLARISASI TERINDUKSI UNTUK IDENTIFIKASI ZONA MINERALISASI GALENA DI DUSUN NGIJU, DESA PURWOHARJO, KECAMATAN KARANG TENGAH, KABUPATEN WONOGIRI, JAWA TENGAH - , FAIZ FIRMANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Geophysical measurement has been conducted by using induced polarization method at Dusun Ngiju, Desa Purwoharjo, Kecamatan Karangtengah, Kabupaten Wonogiri, Central Java. The research aimed to find out and to identify the location and the distribution of galena mineralization zone. Induced polarization measurement was conducted through time domain, by dipole â dipole array. The measurements of the polarization were done in 12 lines with 20 meters spaces between the observed points. The result of the used induced polarization method was resistivity model and rocks chargeability. The models show that resistivity and chargeability of galena in this area was 200 - 500 Ohm and 60 â 150 msec. The Estimation area which is potential to have Galena is about 816.021 m3.